2003
DOI: 10.1007/s000180300013
|View full text |Cite
|
Sign up to set email alerts
|

Increased demyelination and axonal damage in metallothionein I+II-deficient mice during experimental autoimmune encephalomyelitis

Abstract: Metallothioneins I+II (MT-I+II) are antioxidant, neuroprotective factors. We previously showed that MT-I+II deficiency during experimental autoimmune encephalomyelitis (EAE) leads to increased disease incidence and clinical symptoms. Moreover, the inflammatory response of macrophages and T cells, oxidative stress, and apoptotic cell death during EAE were increased by MT-I+II deficiency. We now show for the first time that demyelination and axonal damage are significantly increased in MT-I+II deficient mice dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 64 publications
2
25
0
Order By: Relevance
“…Together with the Zn-MT2 treatment resulting in EAE reduction, this result implicates that MTs have a strong neuroprotective effect within the CNS (28). Moreover, in the absence of MTs, mice exhibited enhanced production of proinflammatory cytokines such as IL-1 and TNF-α, which in turn can lead to inhibition of leukocyte recruitment and ameliorate EAE (29,30). In this study, we established the correlation between MTs and IL-10 production within Tr1 cells and their proinflammatory role in the EAE model.…”
Section: Discussionmentioning
confidence: 81%
“…Together with the Zn-MT2 treatment resulting in EAE reduction, this result implicates that MTs have a strong neuroprotective effect within the CNS (28). Moreover, in the absence of MTs, mice exhibited enhanced production of proinflammatory cytokines such as IL-1 and TNF-α, which in turn can lead to inhibition of leukocyte recruitment and ameliorate EAE (29,30). In this study, we established the correlation between MTs and IL-10 production within Tr1 cells and their proinflammatory role in the EAE model.…”
Section: Discussionmentioning
confidence: 81%
“…CZ produces alterations that are very similar to those exhibited by animal models with an experimental autoimmune encephalomyelitis mimicking the demyelinating human disease multiple sclerosis. With this animal model, a protective role of MT-I/II could be demonstrated, since exogenous administration of the protein significantly prevented demyelination and axonal damage while such effects were significantly increased in MT-I/II-deficient mice [23,24]. Thus, the increase in MT-I/II levels in CZ-treated mice can be related to the defence mechanism against CZ toxicity.…”
Section: Discussionmentioning
confidence: 82%
“…This allowed one to extend the possible spectrum of functions of MT-III protein in the CNS. In addition, studies carried out over the past 10 years showed that genes MT-І and MT-ІІ are expressed in a number of tissues, including those in the CNS, while the expression of genes MT-ІІІ and MT-ІV is characterized by a clear cell specificity [4,5,20].…”
Section: Classification Of Metallothioneinsmentioning
confidence: 98%